THE IMPLEMENTATION OF SPECIALIZED JURISDICTIONAL COURTS FOR THE EFFECTIVE PROCESSING OF COMPUTER CRIMES - Meneses Ochoa, Jean Paul (2026)
This study focuses on the problem associated to the few sentences issued in the Judiciary for cases of cyber offenses, requiring effective attention from the authorities. Thus, in response to what is established in the doctrine regarding special jurisdictions, as well as the effective results obtained in the resolution of certain situations, the target of this research is to expose that the implementation of the jurisdictional bodies specialized in computer crimes would contribute to the effective processing of this type of crimes in the Judiciary. To achieve this, we will examine the statistics related to reported grievances and judgments concerning computer offenses to highlight the issue that needs attention. Then an examination will be carried out of the actions of the Judiciary against computer crimes. Subsequently, a review of the doctrine related to special jurisdictions will be carried out, as well as the criminological contexts that have prompted the Peruvian State to implement specialized jurisdictional bodies for the processing of certain cases. Finally, through an analysis of the opinions of authors who emphasize the necessary specialization of officials for the treatment of computer crimes and the history of specialized jurisdictional bodies that have obtained effective results, it is shown that the implementation of jurisdictional bodies specialized in computer crimes would contribute to the effective processing of this type of crime in the Judiciary.